The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1186/s43556-021-00035-2
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Farnesoid X receptor (FXR) for developing novel therapeutics against cancer

Abstract: Cancer is one of the lethal diseases that arise due to the molecular alterations in the cell. One of those alterations associated with cancer corresponds to differential expression of Farnesoid X receptor (FXR), a nuclear receptor regulating bile, cholesterol homeostasis, lipid, and glucose metabolism. FXR is known to regulate several diseases, including cancer and cardiovascular diseases, the two highly reported causes of mortality globally. Recent studies have shown the association of FXR overexpression with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 231 publications
0
28
0
Order By: Relevance
“…K-Ras is a frequently mutated oncogene in CRC; its diverse mutations promote the activation of the MAPK pathway and cause spontaneous tumor development [ 126 ], and the aberrant activation of the PI3K/Akt/mTOR pathway strongly attenuates the efficacy of MAPK suppression [ 127 ]. It is reported that inhibition of K-Ras signaling in human colon cancer cells resulted in a strong increase in FXR levels [ 115 ] while FXR downregulation has been negatively related with PI3K signaling in human colon cancer [ 128 ].…”
Section: Dysregulated Signaling Pathways In Colorectal Cancer: the Em...mentioning
confidence: 99%
“…K-Ras is a frequently mutated oncogene in CRC; its diverse mutations promote the activation of the MAPK pathway and cause spontaneous tumor development [ 126 ], and the aberrant activation of the PI3K/Akt/mTOR pathway strongly attenuates the efficacy of MAPK suppression [ 127 ]. It is reported that inhibition of K-Ras signaling in human colon cancer cells resulted in a strong increase in FXR levels [ 115 ] while FXR downregulation has been negatively related with PI3K signaling in human colon cancer [ 128 ].…”
Section: Dysregulated Signaling Pathways In Colorectal Cancer: the Em...mentioning
confidence: 99%
“…Because the aberrant activation of the EMT process enhanced malignant progression (including metastasis, invasion, and chemoresistance) of various kinds of cancer cells ( Girisa et al, 2021 ; Cook and Wrana, 2022 ), to evaluate the association of CNTN -1 with malignant progression via EMT, the wound-healing assay, invasion assay, and drug sensitivity assay were carried out and the data showed that CNTN -1 overexpression dramatically enhanced the migration ( Figure 5A ), invasion ( Figure 5B ), and tolerance to cisplatin (A549- CNTN -1 vs. A549- CNTN -1-NC, Figure 5C ). These findings indicated that CNTN -1 upregulation promoted EMT phenotype, which enhanced the malignant progression of A549 cells.…”
Section: Resultsmentioning
confidence: 99%
“…Numerous malignancies, including lung cancer, have been studied using FXR blockade [ 35 ]. In addition, MCA was identified as a naturally occurring FXR antagonist produced by the gut microbiota [ 36 ].…”
Section: Discussionmentioning
confidence: 99%